Parental Polymorphism Survey for Identifying Genes/QTLs for BPH Resistance in Assam Land Race 10-3 - Bhargava, Kadthala; Sreedhar, M.; Vanisri, S.; Rathod, Ramya; Lakshmi, V. Jhansi; Parimala, K. (International Journal of Bio-resource and Stress Management, 2023)
The current research was taken up at Institute of Biotechnology (IBT), PJTSAU, Hyderabad Telangana, India in kharif from August to November, 2021 to access the parental polymorphism between 10-3 and Telangana Sona. 10-3, an Assam landrace, is a bold grain rice variety with high BPH resistance to biotype-4. Whereas, Telangana Sona (RNR 15048) is a short and slender grain variety of rice that is popular among farmers and consumers across Telangana and other Indian states due to its high yield and low glycemic index. Despite being blast resistant, Telangana Sona is susceptible to the insect pest Brown Plant hopper (BPH) Nilaparvata lugens (Stål). The present study aimed to characterize the parental polymorphism between 10–3 and Telangana sona to facilitate mapping of genetic loci linked with BPH resistance in the 10–3 and to optimize the retention of favourable alleles from Telangana sona during marker assisted backcross breeding. Eight hundred and sixteen highly variable Simple Sequence Repeats (SSRs) including thirty-five BPH linked markers covering 12 chromosomes were used to assess DNA polymorphism between 10-3 and Telangana Sona. Out of 816 markers screened, 97 (11.89%) were found to be polymorphic between 10–3 and Telangana Sona of which, 82 were genomic SSRs and 15 were BPH linked markers. Chromosome 6 exhibited highest polymorphism percentage with a value of 30%, indicating that this chromosome is useful in studying parental variation and lowest polymorphism percentage found on chromosome 5 (3.49%). These 97 polymorphic markers will help in construction of linkage map for identifying QTLs linked with BPH resistance and for marker assisted backcrossing breeding in Telangana Sona.